Matching Cue Size and Task Properties in Exogenous Attention. Issue 12 (December 2013) - Burnett, Katherine E.; d'Avossa, Giovanni; Sapir, Ayelet
Exogenous attention is an involuntary, reflexive orienting response that results in enhanced processing at the attended location. The standard view is that this enhancement generalizes across visual properties of a stimulus. We test whether the size of an exogenous cue sets the attentional field and whether this leads to different effects on stimuli with different visual properties. In a dual task with a random-dot kinematogram (RDK) in each quadrant of the screen, participants discriminated the direction of moving dots in one RDK and localized one red dot. Precues were uninformative and consisted of either a large or a small luminance-change frame. The motion discrimination task showed attentional effects following both large and small exogenous cues. The red dot probe localization task showed attentional effects following a small cue, but not a large cue. Two additional experiments showed that the different effects on localization were not due to reduced spatial uncertainty or suppression of RDK dots in the surround. These results indicate that the effects of exogenous attention depend on the size of the cue and the properties of the task, suggesting the involvement of receptive fields with different sizes in different tasks. These attentional effects are likely to be driven by bottom-up mechanisms in early visual areas.